Bank safety under Basel II capital requirements - Jukka Vauhkonen (Bank of Finland, 2009)
We consider the impact of mandatory information disclosure on bank safety in a spatial model of banking competition in which a bank s probability of success depends on the quality of its risk measurement and management systems. Under Basel II capital requirements, this quality is either fully or partially disclosed to market participants by the Pillar 3 disclosures. We show that, under stringent Pillar 3 disclosure requirements, banks equilibrium probability of success and total welfare may be higher under a simple Basel II standardized approach than under the more sophisticated internal ratings-based (IRB) approach.
URN:NBN:fi:bof-20140807152
Keywords: 330